Stakeholders, reciprocity, and firm performance - Bosse, Douglas A.; Phillips, Robert A.; Harrison, Jeffrey S. (Strategic Management Journal, 2009)
Abstract The assumption that economic actors behave in a boundedly self‐interested manner promises fruitful new insights for strategic management. A growing literature spanning multiple disciplines indicates most actors' selfish utility maximizing behaviors are bounded by norms of fairness. Rather than being purely self‐interested, people behave reciprocally by rewarding others whose actions they deem fair and willingly incurring costs to punish those they deem unfair. Economists show that employers who are perceived as distributionally fair by their employees generate comparatively more value due to the positively reciprocal behavior of those employees. The organizational justice literature distinguishes two additional types of fairness assessed by employees. Drawing from both these bodies of work, we employ stakeholder theory to propose how perceptions of fairness result in reciprocity (1) extending to all stakeholders of the firm and (2) affecting firm performance. Copyright © 2008 John Wiley & Sons, Ltd.